Investigation of Neoplastic Cells in the Bone Marrow of Female Dogs with Mammary Gland Tumors - Talita B. Corsini; Paulo H. L. Bertolo; Júlio E. H. Monteiro; Gabriela P. Lima; Letícia Bonato; Cristhian V. Estrada; Fabiana D. L. Rocha; Tiago Prada; Bruna F. Firmo; Maricy A. Ferreira; Andrigo B. De Nardi; Pamela R.R. Moreira; et al. (Journal of Veterinary Healthcare, 2020)
Background The mammary glands are the second most common tumor development site in female dogs. One of the ways of staging such tumors is to evaluate the presence or absence of distant metastasis, including in bone marrow. Such findings in human medicine are associated with poor survival of women with breast tumors. However, in veterinary medicine, this clinical staging is used more for patients with lymphomas and mastocytomas. Studies using bone marrow biopsies as a staging method for mammary tumors are scarce. Objectives The present study was to evaluate mammary lesions and bone marrow in 23 female dogs, searching for disseminated tumor cells or metastatic foci. Results: Grade I carcinoma in mixed tumors was the type most observed (22.4%), and there was no statistical difference in relation to tumor size or presence of metastasis in lymph nodes. In the bone marrow of one female dog with carcinosarcoma (4.35%), there was cytoplasmic marking of a probable disseminated tumor cell of epithelial origin, and immunohistochemical evaluation showed presence of cytokeratin-19 antibodies. None of the female dogs presenting reduced cellularity or medullary fibrosis, confirmed through Masson’s trichrome technique, had cell marking in immunohistochemical analyses. Conclusions Bone marrow evaluation can be used as a staging method for mammary gland tumors in female dogs, since disseminated tumor cells present the potential to become secondary lesions and to disseminate to distant foci, thereby causing tertiary metastases over an indeterminate period of time.
Keywords: Bone marrow biopsy